URDU-ROLE OF SOCIAL INSTITUTIONS IN PREACHING OF RELIGION-STATE RESPONSIBILITIES IN THE LIGHT OF THE PROPHET'S SIRAH - Nimra Sohail; Makhdoom Muhammad Roshan Siddiqui (دی اسکالر)
Societal institutions regulate attitudes and behavioral patterns based on fundamental societal needs. A framework of interrelated social ties and ideals that are established to carry out a significant societal function is known as a social institution. Social institutions are significant for the progress of a society and country. Family, religious, political, and educational institutions play a vibrant part in the proselytization of religion. In this article, the role of social institutions in the evangelization of Islam will be pointed up in Prophet (PBUH)’s sirah and historical conventions. This research will be limited to intimate institutes (family), religious institutes (mosque), and educational institutes (madaris). Qualitative and historical research methods will be applied to analyze the conventions of the Quran and Sunnah related to the matter. State responsibilities for the cause of Dawah will be the key point as the state is foremost responsible for the preaching. This research is crucial as it can provide a framework for contemporary states to utilize their social institutions especially family, mosques, and madaris for the noble cause of dawah.